PERANCANGAN APLIKASI JASA LAUNDRY DENGAN METODE EXTREME PROGRAMMING (XP) BERBASIS ANDROID - Humairani, Ayunda Annisa; Simanjuntak, Pastima (LPPM Universitas Putera Batam, 2023)
One of the businesses that has currently penetrated the market is the laundry business. With a sizable income, the laundry business is increasingly in demand by many people as a main or side business. Viky Laundry is one of the laundry places that has customers every day considering its strategic location, which is near residential areas. Unfortunately, in the process, Viky Laundry still uses manual methods without using a computer system as a tool. Therefore, research was conducted to design an Android-based laundry service application that is more effective and provides time efficiency for the laundry shuttle process, records incoming and outgoing clothes, and provides information about Viky Laundry itself. The research methods used include literature study, interviews, design and testing. The software development model used in this research is the Extreme Programming (XP) method. The technology used, then produced an application where customers easily and practically do the laundry process and laundry owners will more easily receive orders from customers. And for laundry entrepreneurs also with the existence of this application helps in recording incoming and outgoing clothes. Based on the results of interviews, and black box testing, the application made is quite helpful for laundry entrepreneurs and laundry customers.